The risk factors for anxiety amongst health care workers in Primary Health care center during COVID 19 pandemic : (General Practice, 2022)
The coronavirus disease 2019 (COVID 19) pandemickilled millions of people and affected the whole world, includingSerbia. Healthcare workers could not isolate themselvesfrom patients. They worked under adverse and challengingconditions, which could have caused mental healthproblems. This study aimed to identify the risk factors foranxiety in healthcare workers working in Covid wards (CW)of Primary Healthcare center (PHC).Method: This cross-sectional study was conductedamong healthcare workers of the CWs. During the studyperiod, we had a total of 150 completed questionnaires. Descriptivestatistics, Pearson chi-square test, and Pearson correlationwere used to analyze the data. We used SPSS for dataanalysis.Results: Our sample included 150 healthcare workers(HCWs), of whom 86.0% were females, the majority were41-50 years of age (40,0%), and have been working for 21-30 years (32,7%). In our sample, 94,6% HCWs stated theyreceived personal protective equipment (PPE). The resultsrevealed a significant association only between gender andanxiety. Anxiety was higher among females than males. Correlationanalysis indicated the feeling of anxiety was positivelycorrelated with the workload, exhaustion, and familystrain. The feeling of anxiety was not correlated with the feelingof protection. The feeling of protection was in negativecorrelation with family strain.Conclusion: Anxiety was present in HCWs during thepandemic. Gender is the risk factor for anxiety in HCWs whowork in CWs in PHCs.
Keywords: Covid-19; healthcare workers; anxiety; risk factors